Kesetaraan Gender dalam Cerita Putri Mandalika Analisis Tzvetan Todorov - Desak Made Yoniartini (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
Literary work is something special for both the connoisseur and the creator. There are not many literary works that discuss gender equality, this is interesting to research, one of the works that discuss gender equality is the story of Putri Mandalika which is closely related to the " bau nyale" tradition on the island of Lombok. This study uses feminist theory and Tzvetan Todorov's analysis in its discussion. Furthermore, this study uses qualitative methods, data obtained from primary data. The results prove that gender equality has existed and been realized in Indonesia for a long time, this is evidence of gender equality in the story of Putri Mandalika, namely 1) Princess Mandalika is the female king in the Sekar Kuning kingdom replacing the king of Tonjang Beru, 2) Princess Mandalika is the king women who are loved by their people, 3) Putri Mandalika is a woman who has a strong stand and is not easily intimidated by organizations that make decisions.